Potentiality of Tourism and Prospect in Jamunakhadi Simsar Area of Jhapa district - Mishra, Manamaya (Historical Journal, 2020)
This paper entitled "Potentiality Tourism and Prospect in Jamunkhadi Simsar and Tourism" area of Jhapa District, Nepal" is to analyze the potentialities of tourism in this area. Jamunkhadi is one of the most scenic tourist destinations in Jhapa district. It is a land of natural scenery, the rich biodiversity, peaceful environment, ethnic diversity, the rich and diverse culture which attract visitors. The aims of the paper are to identify the prospects, potentiality and promote tourism in this area. The universal sample is Surunga VDC. The local people, hotel owner, domestic visitors and tourism experts, government service holders were the sample respondents and the sample size is only 53 for the study. The data collection method was on both primary and secondary sources. The primary data collected from the structured and semi structure questionnaire by interview schedule and key informants interview also done. There is high potentiality of tourism in Jamunkhadi because it has numerous sightseeing spots, tourism interest places such as the lake, the jungle, the open lane, picnic spot, the mini zoo, the rubber processing center etc. There are many other attractive places around Jamunkhadi Simsar and Tourism Area such as the Mai river and bridge, Domukha, the Mai Mandir, Arjundhara Dham, Satasi Dham, Dhanuskoti Dham, tea gardens etc. It is found that most tourists spend 3 or 4 hours and no tourists spend night in the spot. Generally the visitors are domestic and they spend 200 to 1000 rupees during their stay in this area. The number of foreign tourist is found very low according to the local people. Local people were found very much interested and devoted for promoting tourism in the study area but there seems lack of co-ordination among the government authorities and local promoters and also lack of fund. Jamunkhadi deserves high potentiality of becoming one of the best rural tourism destinations of the country.